2008
DOI: 10.1677/jme-08-0099
|View full text |Cite
|
Sign up to set email alerts
|

Functions of PIT1 in GATA2-dependent transactivation of the thyrotropin β promoter

Abstract: Thyrotropin (TSH) is a heterodimer consisting of a and b chains, and the b chain (TSHb) is specific to TSH. The coexistence of two transcription factors, PIT1 and GATA2, is known to be essential for TSHb expression. Using kidneyderived CV1 cells, we investigated the role of PIT1 in the expression of Tshb gene. GATA2 Zn finger domain, which is known to recognize GATA-responsive elements (GATA-REs), is essential for cooperation by PIT1. Transactivation of TSHb promoter requires PIT1-binding site upstream to GATA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 39 publications
(70 reference statements)
7
32
0
Order By: Relevance
“…First, they showed that as long as T3 is at low concentrations or absent, expression of the TSH gene is maintained by Pit1 and GATA2 without stimulation by TRH signaling (Fig. 7(a)) (Gordon et al, 1997;Kashiwabara et al, 2009;Ohba et al, 2011). In agreement with this, the signaling and the number of TSH -positive cells in the pituitary of TRH-deficient mice were comparable with those of wild-type mice (Shibusawa et al, 2000).…”
Section: Trh-dependent Activation Vs T3/tr-induced Repressionsupporting
confidence: 53%
See 4 more Smart Citations
“…First, they showed that as long as T3 is at low concentrations or absent, expression of the TSH gene is maintained by Pit1 and GATA2 without stimulation by TRH signaling (Fig. 7(a)) (Gordon et al, 1997;Kashiwabara et al, 2009;Ohba et al, 2011). In agreement with this, the signaling and the number of TSH -positive cells in the pituitary of TRH-deficient mice were comparable with those of wild-type mice (Shibusawa et al, 2000).…”
Section: Trh-dependent Activation Vs T3/tr-induced Repressionsupporting
confidence: 53%
“…Thus, cooperation of Pit1 with GATA2 is not synergistic, but Pit1 protects GATA2 from inhibition by SR (de-repression). These findings not only provide an insight as to why TSH expression is restricted in thyrotrophs where Pit1 and GATA2 coexist, but also imply that the true activator that drives the TSH promoter activity is GATA2 but not Pit1 (Kashiwabara et al, 2009). …”
Section: Gata2 Not Pit1 Is the True Activator That Drives The Promomentioning
confidence: 77%
See 3 more Smart Citations